SUPERSTRUCTURE AND SUBSTRUCTURE DESIGN OF SEASIDE FREIGHT TRAIN BRIDGE SECTION TPS - KALIANAK - - Nim: 15014115 , NADIRA
Sea transport services between Java Island and Eastern Indonesia Region mostly served by Tanjung Perak Port in Surabaya City. Inter-island trade conducted in Tanjung Perak shows a significant increase from year to year. The rapid development of container flows in Tanjung Perak cannot be accommodated by the development of supporting infrastructures thus causing congestion. Train is one of the alternative modes of carrying goods that can be used in addition to the current mode. One of the train lines to be built is section TPS to Kaliank station. Both stations will be connected by the sea, thus requiring a bridge as supporting infrastructure. Therefore, the author will design a seaside freight train bridge connecting TPS and Kalianak station in this final project. The superstructure designed from steel material based on economic and efficiency consideration. The design of superstructure including the steel truss structure and hollow pier with Load and Resistance Factor Design (LRFD) method. The programs that used in superstructure modelling are SAP2000 and CSICol. The modelling followed by analysis based on current rules and references. The results of superstructure modelling and analysis are steel profiles, connections of the steel bridge, and dimensions of the reinforced concrete hollow pier. The bridge substructure to be designed is pile foundation. The foundation is designed by calculating the axial and lateral pile capacity with Allowable Stress Design (ASD) method. The axial and lateral capacity of single pile will determine the configuration of group piles. The programs used in pile analysis are Ensoft L-Pile and Ensoft G-Pile. The configuration of a group pile determines the dimensions of the pile cap and the settlement of structure. The results are the configuration of group piles, dimension of pile cap, and the settlement of structure.